Simulation-based cutaneous surgical-skill training on a chicken-skin bench model in a medical undergraduate program - Denadai, Rafael [UNESP]; Saad-Hossne, Rogério [UNESP]; Souto, Luís Ricardo Martinhão (Wolters Kluwer, 2013)
Background: Because of ethical and medico-legal aspects involved in the training of cutaneous surgical skills on living patients, human cadavers and living animals, it is necessary the search for alternative and effective forms of training simulation. Aims: To propose and describe an alternative methodology for teaching and learning the principles of cutaneous surgery in a medical undergraduate program by using a chicken-skin bench model. Materials and Methods: One instructor for every four students, teaching materials on cutaneous surgical skills, chicken trunks, wings, or thighs, a rigid platform support, needled threads, needle holders, surgical blades with scalpel handles, rat-tooth tweezers, scissors, and marking pens were necessary for training simulation. Results: A proposal for simulation-based training on incision, suture, biopsy, and on reconstruction techniques using a chicken-skin bench model distributed in several sessions and with increasing levels of difficultywas structured. Both feedback and objective evaluations always directed to individual students were also outlined. Conclusion: The teaching of a methodology for the principles of cutaneous surgery using a chicken-skin bench model versatile, portable, easy to assemble, and inexpensive is an alternative and complementary option to the armamentarium of methods based on other bench models described. © Indian Journal of Dermatology 2013.
Keywords: Bench model; Chicken; Skills; Student; Surgery; Training; Undergraduate; chicken; education program; feedback system; forelimb; human; incision; laparoscopic scissors; learning; methodology; nonhuman; optical tweezers; pension; scalpel; simulation; skin; skin biopsy; skin surgery; surgical technique; surgical training; suturing method; thigh; trunk; undergraduate student